Mutational Analysis of the Hydrophobic Tail of the Human Immunodeficiency Virus Type 1 p6(Gag) Protein Produces a Mutant That Fails To Package Its Envelope Protein - Ott, David E. (American Society for Microbiology, 1999)
The p6(Gag) protein of human immunodeficiency virus type 1 (HIV-1) is produced as the carboxyl-terminal sequence within the Gag polyprotein. The amino acid composition of this protein is high in hydrophilic and polar residues except for a patch of relatively hydrophobic amino acids found in the carboxyl-terminal 16 amino acids. Internal cleavage of p6(Gag) between Y(36) and P(37), apparently by the HIV-1 protease, removes this hydrophobic tail region from approximately 30% of the mature p6(Gag) proteins in HIV-1(MN). To investigate the importance of this cleavage and the hydrophobic nature of this portion of p6(Gag), site-directed mutations were made at the minor protease cleavage site and within the hydrophobic tail. The results showed that all of the single-amino-acid-replacement mutants exhibited either reduced or undetectable cleavage at the site yet almost all were nearly as infectious as wild-type virus, demonstrating that processing at this site is not important for viral replication. However, one exception, Y36F, was 300-fold as infectious the wild type. In contrast to the single-substitution mutants, a virus with two substitutions in this region of p6(Gag), Y36S-L41P, could not infect susceptible cells. Protein analysis showed that while the processing of the Gag precursor was normal, the double mutant did not incorporate Env into virus particles. This mutant could be complemented with surface glycoproteins from vesicular stomatitis virus and murine leukemia virus, showing that the inability to incorporate Env was the lethal defect for the Y36S-L41P virus. However, this mutant was not rescued by an HIV-1 Env with a truncated gp41(TM) cytoplasmic domain, showing that it is phenotypically different from the previously described MA mutants that do not incorporate their full-length Env proteins. Cotransfection experiments with Y36S-L41P and wild-type proviral DNAs revealed that the mutant Gag dominantly blocked the incorporation of Env by wild-type Gag. These results show that the Y36S-L41P p6(Gag) mutation dramatically blocks the incorporation of HIV-1 Env, presumably acting late in assembly and early during budding.